Respuesta :
Answer:
a_n=-\frac{1}{4 a_{n-1}
Step-by-step explanation:
The recursive formula for the geometric sequence is given by:
a_n = a_{n-1} \cdot r
where,
r is the common ratio terms
-16, 4, -1, ...
This is a geometric sequence.
Here, and
Since,
ans so on .....
Substitute the given values we have;
⇒
Therefore, the recursive formula for the following geometric sequence is,
Answer:
[tex]A_n= A_{n-1} (\frac{-1}{4})[/tex]
Step-by-step explanation:
Formulate the recursive formula for the following geometric sequence.
{-16, 4, -1, ...}
Here the common difference of two terms are not same.
LEts find the common ratio. To find common ratio, divide the second term by first term
[tex]\frac{4}{-16} =\frac{-1}{4}[/tex]
[tex]\frac{-1}{4} =\frac{-1}{4}[/tex]
So common ratio is -1/4
Recursive formula is
[tex]A_n= A_{n-1} (r)[/tex]
'r' is the common ratio.
Recursive formula becomes
[tex]A_n= A_{n-1} (\frac{-1}{4})[/tex]